Tectonic evolution of the Atlantic rift, central sector offshore Uruguay - Marmisolle, Josefina (2025)
The Uruguayan Continental Margin (UCM) is considered one of the most promising frontier areas for hydrocarbon exploration in the South Atlantic. The UCM central sector, corresponding to the transitional region between the Punta del Este and Pelotas basins and where the Rio de la Plata Transfer System(RPTS) is located, exhibits outstanding characteristics such as interruption of the seaward dipping reflectors (SDRs), dislocation of magnetic and gravity anomalies and depocenters, and hyper-thinning of the continental crust. Owing to these characteristics, this sector is a key area for understanding the evolution of the margin during the Atlantic opening and evaluating the real potential of the UCM to contain hydrocarbon accumulations. This study demonstrates the results of a new subsurface mapping method using 2D and 3D seismic data in the central sector of the UCM. Structural interpretations have led to the definition of i) an NW-oriented hyperextended region located where the SDRs are interrupted, characterized by a shallow Moho (˂3 km); ii) a set of NW-SE oriented transtensional faults, some of which reach the Moho, which has delineated a series of discrete grabens; and iii) a Barremian-Aptiandepocenter with a rhomboidal geometry, exhibiting the greatest thickness over the hyperextended crust region. The central sector of the UCM concentrates on the extensional processes associated with the breakup of Western Gondwana, which controlled the initial phase of the Atlantic opening in this region. The sinistral transcurrent nature of the RPTS plays a crucial role in generating the transtensional stress field in an extensive regional context. This process reactivates basement-inherited structures with a general NW-SE orientation, leading to the formation of subsidence areas. The proposed new tectonic model will contribute to the knowledge of the hydrocarbon potential of the UCM.